2009
DOI: 10.1097/mpg.0b013e31818f0a0d
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Is Associated With Low Serum Ferritin Levels in Israeli Arab Children—A Seroepidemiologic Study

Abstract: We examined the association between Helicobacter pylori seropositivity and low ferritin levels in sera of 509 Israeli Arab children aged 1 to 19 years. Serum ferritin levels were measured using the immunoturbidity assay. ELISA was used to detect serum IgG antibodies to H pylori and IgG antibodies to H pylori CagA strains. Low ferritin level was found between 14.5% and 8.6% of the H pylori seropositive and seronegative participants, respectively (P = 0.035). A trend for a higher frequency of low ferritin was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 19 publications
4
35
0
Order By: Relevance
“…They were also consistent with findings of Muhsen et al who found that H. pylori is associated with reduced iron stores [22]. This was confirmed in a more recent study [23]. Also, the findings of Cardenas et al support the present results.…”
Section: Discussionsupporting
confidence: 95%
“…They were also consistent with findings of Muhsen et al who found that H. pylori is associated with reduced iron stores [22]. This was confirmed in a more recent study [23]. Also, the findings of Cardenas et al support the present results.…”
Section: Discussionsupporting
confidence: 95%
“…In a community-based study among Arab children in Israel, we found significantly lower mean hemoglobin levels in children ages 6–9 years who were infected with H. pylori compared with their uninfected peers 66,7. In a systematic review and meta-analysis,8 we found higher prevalence of IDA in H. pylori -infected subjects than uninfected ones (pooled odds ratio = 2.8; 95% confidence interval = 1.9–4.2) 8…”
mentioning
confidence: 80%
“…Major population surveys conducted over diverse geographic areas [16][17][18][19][20][21][22][23] indicate that H pylori positivity is associated with an increased prevalence of iron deficiency, and meta-analysis of 19 observational epidemiologic studies and 6 interventional trials revealed an increased risk for IDA with a pooled odds ratio (OR) of 2.8 among H pylori-infected subjects. 24 Meta-analysis of 16 randomized trials involving 956 patients with documented H pylori infection and IDA showed that the increments from baseline to end point in Hb, serum iron, and serum ferritin were significantly higher with anti-H pylori treatment plus oral iron compared with oral iron alone.…”
Section: H Pylori Gastritismentioning
confidence: 99%